Intellectual-Social Dynamics at State Islamic University in Indonesia: The Role of Alumni of Islamic Boarding Schools from Bangka Island - Sulaiman, Rusydi; Yanasari, Pebri (Madania: Jurnal Kajian Keislaman, 2022)
This article aims to sense the intellectual and social dynamics of alums of Islamic boarding schools or the pesantren from Bangka Island and their role in State Islamic University, PTKIN in Indonesia. These issues are analyzed with Linton's role theory. This qualitative research takes primary data from eight informants, while secondary data is taken from other informants as an addition. The data was collected through observation, semi-structured interviews, and documentation. The "Snow-ball Sampling" method obtained 57 informants and narrowed them down to eight. In addition, they were analyzed using three stages: orientation, exploration, and focus study. The results of this study explain that there are eight people from Bangka Island as alumni of the pesantren who have been currently taking part in PTKIN throughout Indonesia by occupying strategic positions and having significant influence in them, such as Prof. Dr. Zulkifli, M.A (Deputy Chancellor 1 of UIN Syarif Hidayatullah Jakarta), Dr. Zayadi, M.Ag (Chancellor of IAIN SAS Babel), Prof. Dr. Hatamar Rasyid (Deputy Chancellor 2 of IAIN SAS Babel), Dr. Misdar, M.Ag (Dean of the Faculty of Sharia IAIN SAS BABEL), Prof. Rohimin, M.Ag (Director of Postgraduate Program at UIN Fatmawati Sukarno Bengkulu), Dr. Muhamad Fauzi, M.Ag, (Deputy Dean 1 of Tarbiyah Faculty at UIN RAFA Palembang), Dr. Abdurrahmansyah, M.Ag (Head of Islamic Studies Program at UIN RAFA Palembang), Dr. Ahmad Izzan (Senate Secretary of the Ethics Commission of UIN Sunan Gunung Djati Bandung). These academics became real examples of intellectual and social dynamics of pesantren graduates from Bangka Island who succeeded in participating in their respective PTKINs. Artikel ini bertujuan untuk mengidentifikasi dinamika sosial intelektual alumni pondok pesantren asal pulau Bangka dan peran mereka di PTKIN. Permasalahan tersebut dianalisis dengan teori peran ala Linton. Penelitian ini termasuk penelitian kualilatif yang mengambil sumber data primer dari delapan informan, sedangkan data sekunder diambil dari informan lain sebagai tambahan. Cara menentukan informan mlalui, “Snow-ball Sampling” didapatkan 57 informan dan mengerucut menjadi delapan. Penggalian data dilakukan dengan observasi, wawancara semi-terstruktur, dan dokumentasi. Data yang didapatkan dianalisis dengan menggunakan tiga tahapan, yaitu orientasi, eksplorasi, dan studi terfokus. Hasil penelitian ini menjelaskan bahwa terdapat delapan orang asal Pulau Bangka sebagai alumni pondok pesantren yang saat ini berkiprah di PTKIN se-Indonesia dengan menduduki posisi strategis dan memiliki pengaruh penting di dalamnya seperti Prof. Dr.Zulkifli, M.A (Wakil Rektor 1 UIN Syarif Hidayatullah Jakarta), Dr. Zayadi, M.Ag (Rektor IAIN SAS Babel), Prof.Dr.Hatamar Rasyid (Wakil Rektor 2 IAIN SAS Babel), Dr.Misdar, M.Ag (Dekan Fak.Syariah IAIN SAS BABEL), Prof. Dr. Rohimin, M.Ag (Dir.Pascasrjana UIN Fatmawati Sukarno Bengkulu), Dr. Muhamad Fauzi, M.Ag, (Wakil Dekan 1 Tarbiyah UIN RAFA Palembang), Dr. Abdurrahmansyah, M.Ag (Kaprodi Studi Islam Pascasarjana UIN RAFA Palembang), Dr. Ahmad Izzan (Sekretaris Senat Komisi Etik UIN Sunan Gunung Djati Bandung). Para akademisi tersebut menjadi contoh nyata dalam perhelatan dinamika sosial intelektual lulusan pesantren asal Pulau Bangka yang berhasil berkiprah di PTKIN-nya masing-masing.